The empirical evidence of voluntary disclosure in the annual reports of listed companies: the case of Thailand - Sukthomya, Duraya (2011)
This study seeks to answer the question of how to explain voluntary disclosure of companies listed on an emerging capital market. It intends to investigate the extent of voluntary disclosure especially that of Thai listed companies, and the influence of company characteristics, financial attributes, and corporate governance related factors on voluntary disclosure practices.